Analisis Penerapan Project Based Learning Dalam Pembelajaran di PAUD - Utari Aprilliya; Riskha Hanifa (Jurnal Al-Fatih, 2026)
This study aims to analyze the implementation of the Project Based Learning (PjBL) model in Early Childhood Education (PAUD) learning and identify its impact on children's engagement and development. The research method used is a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, interviews, and documentation of teachers and students in PAUD units. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of PjBL in PAUD learning can increase children's activeness, creativity, and social skills through contextual and meaningful project-based activities. In addition, teachers act as facilitators who guide children in the process of exploring and completing projects. However, there are several obstacles such as limited time and teacher readiness in designing projects that are appropriate to the characteristics of early childhood. In conclusion, the Project Based Learning model is effectively implemented in PAUD learning because it can create a fun and meaningful learning experience, and support the optimal development of children's cognitive, social, and emotional aspects.